Filsafat Ketuhanan Vaiṣṇava Perspektif Pemikiran Caitanya Mahāprabhu: Doktrin Acintya Bhedābheda dan Budaya Bhakti dalam Teks Śrī Śikṣāṣṭakam - Ni Kadek Surpi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Śri Caitanya is considered a reformer in Vaiṣṇava philosophy. He, who lived in the 15th century, is considered to have a strong influence on the culture of devotion to the modern age. However, despite being known as a brilliant young scientist, Śri Caitanya left behind only eight verses, which are called Śikṣāṣṭaka. These eight verses clearly reveal His mission and teachings. The disciples in his disciplinary line wrote many works to explain Caitanya's teachings, which were mostly conveyed orally. The Acintya Bhedābheda is a central doctrine that is regarded as a synthesis of the different principles in Vaiṣṇava philosophy. Caitanya asserts that there is an incomprehensible difference, as well as an incomprehensible indifference (Acintya Bhedābheda). Thus, he clung to the divine unity, which sustained large popular worship of murti worship. Caitanya affirmed the bhakti-Vedānta philosophy's excellence to strengthen the fight against the Maya vada doctrine of Sankara philosophy.